2004
DOI: 10.1111/j.1365-2559.2004.01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinomas arising in multilocular thymic cysts of the neck: a clinicopathological study of three cases

Abstract: The cases described here represent an unusual variant of carcinoma arising in multilocular thymic cyst in the neck region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Likewise, MTCs have been described in patients with Sjögren’s disease 123,127 . Malignant epithelial tumours, both typical thymomas as well as carcinomas of various subtypes, have been reported to occur within MTCs 123,128–130 . However, in the series of 18 MTCs reported by Suster and Rosai, four cysts were found to harbour a thymoma or carcinoma, suggesting that rather than true incidental findings, the tumours were probably causative to the formation of the cyst in the first place.…”
Section: General Remarksmentioning
confidence: 99%
“…Likewise, MTCs have been described in patients with Sjögren’s disease 123,127 . Malignant epithelial tumours, both typical thymomas as well as carcinomas of various subtypes, have been reported to occur within MTCs 123,128–130 . However, in the series of 18 MTCs reported by Suster and Rosai, four cysts were found to harbour a thymoma or carcinoma, suggesting that rather than true incidental findings, the tumours were probably causative to the formation of the cyst in the first place.…”
Section: General Remarksmentioning
confidence: 99%
“…The non-neoplastic entities include thymic hyperplasia, cystic change and many others. Thymic cysts are very deceptive as thymomas or carcinomas are known to undergo cystic change10. In adults, the most common mediastinal tumour is thymoma11, followed by lymphoma, although some studies have reported lymphoma as the most common mediastinal tumor456.…”
Section: Discussionmentioning
confidence: 99%
“…We found only three documented cases in our hospital files over a period of 15 yr. Only eleven other BTCs have been previously reported in the surgical pathology literature as part of a series or as case reports (Table II). [3][4][5][6][7][8][9] The mean age of presentation is 62 yr, including our current cases. 7 The male-to-female ratio is 8:5.…”
Section: Discussionmentioning
confidence: 99%